Production of Rayon Grade Pulp from Moringa oleifera - Mahajan, Sushma; Sharma, Y. K. (Indian Forester, 1984)
Present study for the production of rayon grade pulp from Moringa oleifera (M. oleifera) by probydrolysed sulphate process shows that M. oleifera is a suitable raw material for the production of high alpba cellulose pulps for use in cellopbane and textile.